Associations of serum 25-Hydroxyvitamin D with overall and breast cancer-specific mortality in a multi-ethnic cohort of breast cancer survivors - Villaseñor, Adriana (2013)
PURPOSE: Despite limited evidence on the association of vitamin D with outcomes in breast cancer survivors, some clinicians advise breast cancer patients to use vitamin D supplements. More evidence is needed to inform these recommendations. METHODS: In the Health, Eating, Activity and Lifestyle Study, we examined associations of post-treatment serum concentrations of 25-hydroxyvitamin D (25(OH)D) on overall and breast-cancer-specific mortality in 585 breast cancer survivors from western Washington State, New Mexico, and Los Angeles County. 25(OH)D was measured in stored blood collected 2 years post-enrollment. Outcomes were ascertained from the Surveillance, Epidemiology, and End Results registries and medical records. Cox proportional hazards models were fit to assess associations of serum 25(OH)D with overall and breast-cancer-specific mortality. RESULTS: After a median follow-up of 9.2 years; 110 women died, including 48 from breast cancer. Standard cut points classified 211 (31.6%) women as serum 25(OH)D deficient (<20 ng/mL), 189 (32.2%) as insufficient (20–30 ng/mL), and 185 (36.2%) as sufficient (>30 ng/mL). Compared to women with deficient 25(OH)D, those in the sufficient ranges had a decreased risk of overall mortality (age-adjusted HR=0.58; 95%CI 0.36–0.96); however multivariate adjustments attenuated the association (HR=0.90; 95%CI 0.50–1.61). No association was found between serum 25(OH)D and breast-cancer-specific mortality (sufficient: HR=1.21; 95%CI 0.52–2.80) in multivariate models. CONCLUSION: In this breast cancer cohort, higher serum 25(OH)D may be associated with improved survival, but results were not statistically significant and must be interpreted with caution. The potential prognostic effect of vitamin D from diet, supplements or both should be evaluated in future larger studies with additional endpoints from breast cancer patients.